An evaluation of buparlisib for the treatment of head and neck squamous cell carcinoma. (22nd January 2021) - Lenze, Nicholas; Chera, Bhisham; Sheth, Siddharth
ABSTRACT: Introduction: Five-year overall survival for head and neck squamous cell carcinoma (HNSCC) is relatively poor at around 50–66%, and there has been little improvement over the past several decades. PIK3CA alterations are common in HNSCC and offer a promising therapeutic target. Areas covered: The authors discuss the PIK3 pathway and the use of PIK3 inhibitors in cancer, with a particular focus on HNSCC. A summary of the safety and efficacy of buparlisib, a class I pan-PI3K inhibitor, from several phase I and phase II HNSCC trials is provided. Expert opinion: With a maximum tolerated dose of 100 mg/day and an acceptable toxicity profile, buparlisib may be effective in HNSCC, irrespective of PIK3CA mutational status. On-going clinical trials will help determine the developmental strategy of buparlisib while novel combinatory strategies including combination with immune checkpoint inhibitors should be considered. Importantly, biomarker strategies, including wider use of tumor sequencing and circulating tumor DNA, should be utilized to improve patient selection.